IMPLEMENTATION OF THE MARKET PLACE LEARNING METHOD ASSISTED BY CANVA TECHNOLOGY MEDIA IN IMPROVING THE LEARNING OUTCOMES OF ISLAMIC CULTURAL HISTORY AT MTS DARUL AMANAH BEDONO - Raihan Hisyam; Mustafidin, Ahmad (EDUCATIVA, 2025)
Islamic Cultural History (SKI) learning at the junior Islamic school (Madrasah Tsanawiyah) level often faces challenges such as low student interest and participation due to passive and conventional teaching methods. This study aims to address these issues by applying the Market Place learning method combined with Canva as a visual aid to improve student learning outcomes and engagement. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were ninth-grade students at MTs Darul Amanah Bedono during the even semester of the 2024/2025 academic year. Data were collected through observation, interviews, documentation, and learning outcome tests. The results showed a significant improvement in student learning mastery, increasing from 31% in the pre-cycle to 54% in Cycle I and reaching 100% in Cycle II. Moreover, students demonstrated growth in cognitive, affective, and psychomotor aspects, including active participation in discussions, the ability to present ideas using visual media, and increased enthusiasm during learning activities. Canva proved to be an effective tool for presenting content in a creative and engaging manner, supporting more contextual and meaningful learning experiences. In conclusion, the Market Place method assisted by Canva not only effectively enhances learning outcomes but also fosters an interactive, collaborative, and enjoyable learning environment. This strategy is recommended for broader implementation in SKI and other subjects, particularly those that are abstract or historical in nature, to promote active engagement and deeper student understanding.